FAKTOR DETERMINAN PELAKSANAAN INISIASI MENYUSU DINI (IMD) OLEH BIDAN DI KABUPATEN BREBES - Alfi, Ziyadatul Chusna Almabruroh Yuni; Susiloretni, Kun Aristiati; Ngadiyono, Ngadiyono; Mardiyono, Mardiyono (RSUP Dr. Kariadi, 2021)
Background: One of the roles and functions of being a midwife is as an implementer, in which of being a health worker assisting in delivery assistance and has an important role to facilitate the mother in the successful implementation of Early Breastfeeding Initiation (Inisiasi Menyusui Dini or IMD). Delivery aids are performed by health personnel who possess midwifery competencies in Brebes Regency for about 98.30%. The percentage of early breastfeeding initiation in Brebes was 40.39%. Purpose: The purpose of this research is to know and analyze the determinant factors early breastfeeding initiation (IMD) implemented by midwives working for Public Health Center (Pusat Kesehatan Masyarakat or Puskesmas) in the working area of ??Brebes Regency Health Office. Methods: This type of research is observational research with survey method and cross sectional approach. The research instrument uses a structured questionnaire that has been tested for its validity and reliability. The research also uses bivariate analysis with chi-square test and multivariate analysis with logistic regression test. The sample is 213 respondents of village midwives in Brebes Regency. Results: The results of logistic regression test showed that the variables affecting the implementation of early breastfeeding initiation were midwife age (OR 0.026 CI 95% 0,0050-0,14), training (OR 2.77 CI 95% 1,29-5,97 ) and duration of work (OR 9.63 CI 95% 3.85-24.1). While the factors that are not related to the implementation of IMD is the attitude, refreshing training, support, and policy superiors. Conclusion: It can be concluded that the most influential variable on initiation of early breastfeeding is length of work (OR 9.63 CI 95% 3,85-24,1).